2018
DOI: 10.3390/ijerph15122770
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Weight Gain and Cardiovascular Fitness Loss over the Summer

Abstract: The purpose of this study was to examine the impact of summer breaks on the body composition and cardiovascular fitness of elementary school children who participated in a multi-year school-based physical activity intervention. Participants were 404 children who had their height and weight measured and completed the Progressive Aerobic Cardiovascular Endurance Run (PACER) during physical education classes at the beginning and end of the school year for three consecutive years. To examine the effects of time on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…6 Recently, two studies have highlighted a concern that the improvements in weight status and aerobic fitness garnered during a school physical activity intervention were lost during the 12-week summer break. 7,8 Weaver et al 9 have suggested that one of the reasons that we have struggled to address childhood obesity is that we have primarily focused on school programming and neglected the 3-month summer break during which children are not in school. In fact, Brazendale et al 10 suggest that these changes in weight status and fitness over the summer could be attributed to the structured day hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, two studies have highlighted a concern that the improvements in weight status and aerobic fitness garnered during a school physical activity intervention were lost during the 12-week summer break. 7,8 Weaver et al 9 have suggested that one of the reasons that we have struggled to address childhood obesity is that we have primarily focused on school programming and neglected the 3-month summer break during which children are not in school. In fact, Brazendale et al 10 suggest that these changes in weight status and fitness over the summer could be attributed to the structured day hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…This is a valid and reliable test that has been used previously to assess cardiovascular fitness in children (Leger & Lambert, 1982 ; Meredith & Welk, 2013 ). Further, previous studies have used the PACER to assess cardiorespiratory fitness in children during the summer months (Brusseau & Burns, 2018 ). It is a feasible test when aiming to analyze large cohorts in a short amount of time as many children can participate at once.…”
Section: Methodsmentioning
confidence: 99%
“…Of the studies measuring adiposity, 84% (21/25) found an increase over the summer [ 9 , 31 , 32 , 35 , 37 , 43 , 45 , 47 , 49 , 52 , 54 , 61 , 64 , 73 , 74 , 75 , 76 , 85 , 86 , 93 , 96 , 99 , 100 , 101 ]. Two studies (8%, 2/25) displayed mixed results [ 26 , 95 ] and two more showed a decrease in adiposity over the summer [ 39 , 104 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Where data were available, comparisons were made between the rates of change in the summertime compared to the rest of the school year. The pattern remained: Of the 22 studies that measured changes in adiposity across both the summer and school periods, 14 studies (64%) found comparatively greater rates of weight gain over the summer [ 9 , 35 , 36 , 37 , 43 , 47 , 54 , 64 , 73 , 74 , 75 , 76 , 85 , 92 , 93 , 96 , 99 , 100 , 101 ], seven (32%) found no difference [ 26 , 31 , 45 , 52 , 61 , 86 , 104 ] and one (4%) found smaller rates of gain [ 39 ]. Regarding CVF, the results were split between declines and mixed results, with five studies (45%) each showing declines [ 26 , 31 , 49 , 52 , 80 ] or mixed/neutral results [ 17 , 32 , 37 , 81 , 86 , 93 ] and only one study demonstrating an improvement [ 43 ].…”
Section: Resultsmentioning
confidence: 99%